Micronutrient supplementation among adults following restrictive diets in Riyadh: a cross-sectional study - Aldahash, Rehab; Alturki, Haifa; Dabbour, Joury; Aldossari, Shahad; Alonazi, Shahad; Aldhfayan, Sarah (Frontiers in Nutrition, 2026)
BackgroundThe growing adoption of restrictive dietary regimens has raised concerns regarding micronutrient adequacy; however, evidence from Saudi Arabia remains limited.MethodsA cross-sectional study was conducted among 400 Saudi adults aged 18–45 years living in Riyadh between December 2024 and March 2025. Participants completed a validated online questionnaire capturing sociodemographic characteristics, dietary regimen, and micronutrient supplementation patterns. Statistical analyses comprised descriptive statistics, the chi-squared test, and Fisher’s exact tests to assess associations between dietary regimens and supplement use, and a multivariable logistic regression analysis to evaluate the association between diet adherence duration and micronutrient consumption.ResultsOverall, 45.1% of participants reported using micronutrient supplements. Vitamin D was the most frequently consumed vitamin, while iron was the most commonly used mineral across all diet types. Supplement use was highest among individuals following gluten-free (75%), ketogenic (66.7%), and low-carbohydrate (64.1%) diets. Significant associations were identified between specific dietary regimens and supplementation with vitamins A, D, K, and B12 and minerals, including calcium, potassium, and selenium. Additionally, longer adherence to certain dietary regimens, particularly intermittent fasting and the combined “Other Diets” group, was significantly associated with higher odds of micronutrient supplementation.ConclusionMicronutrient supplementation is highly prevalent among individuals following restrictive diets in Riyadh, with specific regimens such as gluten-free, ketogenic, and low-carbohydrate diets showing greater dependence on supplements. Moreover, the increased likelihood of supplement use among individuals adhering to certain diets for longer durations highlights the significance of monitoring nutritional adequacy over time. These findings underscore the need for targeted dietary counselling and public health strategies that promote balanced nutrition according to popular diet trends.